(untitled) (Mutah Journal of Humanities and Social Sciences (MJHSS), 2025)
This study addresses a fundamental issue of analogy, which is “justifying multiple rulings with a single reason” according to Shafi’i fundamentalists. The study clarified the concept of explaining multiple rulings with a single reason, then showed how the Shafi’i fundamentalists dealt with clarifying the subject of the dispute in this study, as the rulings include three different types: identical rulings, contradictory rulings, and different rulings. The subject of the dispute in the issue lies in the third type of ruling, which is: the multiplicity of different, non-contradictory rulings. The opinions of the Shafi’i fundamentalists differed on this issue. Some of them permitted the multiplicity of rulings and some of them prohibited that, but the research concluded in its result that the disagreement is in fact verbal, so the multiplicity of rulings one reason is not impossible. This has been demonstrated by presenting some of the jurisprudential applications of Shafei’s on the permissibility of justifying more than one legal ruling with one reason.